2020
DOI: 10.3892/ijmm.2020.4529
|View full text |Cite
|
Sign up to set email alerts
|

Osteoking improves OP rat by enhancing HSP90‑β expression

Abstract: Osteoporosis (OP) is a chronic bone disease that affects individuals worldwide. Osteoporosis is primarily asymptomatic, and patients with OP suffer from pain, inconvenience, economic pressure and osteoporotic fracture (OPF). Osteoking, a Traditional chinese Medicine compound that originates from the Yi ethnic group, has been used for a number of years to treat fractures. In our previous study, osteoking exhibited therapeutic effects on rats with OPF by promoting calcium deposition. Based on bioinformatics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…A DXA method was used to evaluate BMD in this study, and an OP model was successfully reproduced, as there was a statistically significant difference in BMD between the groups. This study reproduced OP rats at 23 weeks after OVX surgery [ 18 ], and intestinal contents were collected on days 0 and 70. In a previous study with estrogen deficiency induced by ovariectomy, Escherichia coli increased without the inhibition of estrogen [ 19 ], and it is known that intestinal microbes have an influence on maintenance of the balance of the bone microenvironment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A DXA method was used to evaluate BMD in this study, and an OP model was successfully reproduced, as there was a statistically significant difference in BMD between the groups. This study reproduced OP rats at 23 weeks after OVX surgery [ 18 ], and intestinal contents were collected on days 0 and 70. In a previous study with estrogen deficiency induced by ovariectomy, Escherichia coli increased without the inhibition of estrogen [ 19 ], and it is known that intestinal microbes have an influence on maintenance of the balance of the bone microenvironment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…), Honghua ( Carthamus tinctorius L.), Sanqi ( Radix Notoginseng ), Duzhong ( Eucommiae Cortex ), Yangjinhua ( Daturae Flos ), Zuandifeng ( Schizophragma integrifolium ), and Biejia ( Trionycis carapace ). Previous studies have demonstrated that osteoking exerts anti-OP effects in OP rat models ( Sun et al, 2020a ; Sun et al, 2020b ). In addition, it has been found that osteoking anti-OP may be through reduction of reactive oxygen species ( Qin et al, 2019 ) or regulating rat bone marrow mesenchymal stem cell osteogenic and adipogenic differentiation ( Yu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 98%
“…OK reduces osteocalcin levels, improves bone density and strength, and prevents osteoporosis in ovariectomized rabbits [13]. OK increase bone ALP levels in OP model rats by enhancing HSP90-β expression and protecting MC3T3-E1 cells from oxidative stress to improve OP [11,14]. Meanwhile, the potential of various natural medicines in reducing blood sugar in the prescription, including the active components of Carthamus tinctorius L, Panax ginseng C.A.Mey., Panax notoginseng (Burkill) F.H.Chen, Astragalus mongholicus Bunge and Citrus reticulata Blanco.…”
Section: Introductionmentioning
confidence: 99%